A new species of Trichomycterus (Siluriformes: Trichomycteridae) from the Andean Cordillera of Perú, with comments on relationships within the genus - Fernández, Luis; Chuquihuamaní, Roberto Quispe (Zootaxa, 2007)
Trichomycterus megantoni, new species, is described from several localities on the Andes of Perú at 1,360 to 2,200 m elevation. The new species differs from all congeners in the possession of autapomorphic characters: ventral interopercle with thickened integument and a reduced foramen in the frontal-supraoccipital. It is further distinguished by the following combination of characteristics: the tip of the pelvic fin when depressed does not reach the anus, the presence of a premaxilla rectangle, the first dorsal fin pterygiophore insertion at or posterior to vertebra 19 to 21, the supraorbital canal with pore 3, the outer tooth row with conic teeth, the head muscles not hypertrophied, the first pectoral fin ray prolonged as thin short filament, the possession of 17 pairs of ribs on each side, and 37 to 40 vertebrae.